ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMEN DALAM MEMILIH PERGURUAN TINGGI (Studi Kasus Pada Universitas Muhammadiyah Magelang) - Zuhriyah, Eny; Ratri, Retno Wahyuning (Universitas Muhammadiyah Magelang, 2006)
This research aim to analyze factors influencing consumer behavior in choose Collage Private sector (Case Study at Universitas Muhammadiyah Magelang), and also look for most dominant factor. Population in this research is new student of University Muhammadiyah Magelang generation 2005/2006. Sample in this research amount to 100 technique and respondent intake of sample with two phase, first pase with purposive sampling and both of accidental sampling. Examination done/conducted by using doubled regression analyzer with significant level 5%. Result of examination to simultan hypothesis indicate that this regression madel have F count/calculate 25.189 with df 1 = 5 and df 2 = 94 is so that got by f value of is tables of 2.311, because F count/calculate (25.189) > (2.311) F of is tables of, hence Ho refused or can be concluded that variable of is Expense Of (X1), Product (X2), Location (X3), Facility (X4), and Promotion (X5) (it) is true by simultan have an effect on significant to Behavior Consumer in choose PTS (Y). Level of the free variable influence to consumer behavior in choose PTS can know seen determinacy coefficient equal to 61,1% and the rest 38,9% influenced by other variable which do not be packed into this research. Result of examination to partial hypothesis indicate that by partial is / individual; free variable of Expense, Product, Location, Facility, and Promotion have an effect on by significant to Brhavior Consumer in choose PTS is variable of is Expense of Result of this research can be concluded taht expense, product, location, promotion and facility represent variable considered by student candidate in choose PTS. From is fifth of existing variable in the reality most dominant variable is expense. Hence to influence consumer so that/ to be choose to enter UMM, UMM require to consider again in determining the expense of education so that/ to be remain to be reached, altought each; every period of is expense of education always experience of improvement and change. This research still have the character of early and need furthermore research by enlarging sample and add research variable.